2005
DOI: 10.1093/rpd/nci330
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plutonium exposures for an epidemiological study of US nuclear workers

Abstract: An ongoing case-control study evaluating the association between workplace external radiation exposures and leukaemia mortality required an assessment of internal plutonium exposures as a potential confounder. Of the study participants, 1,092 were employed at four Department of Energy sites where plutonium-bearing materials were processed or stored. Exposures were assessed by first categorising exposure potentials based on available bioassay data, then estimating doses for workers in the highest categories usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Missed internal and external dose during the early years of operation is a possibility. Detection levels for plutonium were relatively high during the 1940s (22), and monitoring did not occur for all potentially exposed workers. Although worker entry into the study required at least one badge monitoring measurement, not every worker was monitored continuously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missed internal and external dose during the early years of operation is a possibility. Detection levels for plutonium were relatively high during the 1940s (22), and monitoring did not occur for all potentially exposed workers. Although worker entry into the study required at least one badge monitoring measurement, not every worker was monitored continuously.…”
Section: Discussionmentioning
confidence: 99%
“…Information on available plutonium compounds, bioassay methods, sample collection frequencies, chemical extraction and recovery, counting techniques, reporting requirements, detection levels, and incidence or confirmation of plutonium deposition was used to develop thresholds for exposure categories. Internal dose for each case and control receiving positive plutonium deposition was assessed through the cutoff date, using methods described elsewhere (22).…”
Section: Radiological Variablesmentioning
confidence: 99%
“…The diverse characteristics of ionising radiation exposures and wide variety of dosimetry practices among facilities and over time necessitated facility‐ and job‐specific adjustments to individual reported exposures to ensure comparability. Therefore, we developed methods to account for recognised biases in the measurement processes that arise from exposure to heterogeneous radiation fields, calibration methods, dosimeter design, dosimeter energy response, and geometry of the critical organ (Daniels & Schubauer‐Berigan, 2005; Daniels & Yiin, 2006; Daniels et al , 2006). We then normalised exposure variables to the individual tissue equivalent dose, where the specified tissue is active bone marrow, to account for differences in radiation types.…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed worker medical records and site records to determine x‐ray examination frequencies, techniques, and equipment specifications (Anderson & Daniels, 2006). Although overall exposures to internally deposited radionuclides were expected to be small in these cohorts, we evaluated potential systemic deposition (as estimated by urinary excretion) and subsequent dose to the bone marrow from plutonium, given its use in study facilities (other than PNS) and high dose per unit intake relative to other internal agents, as described elsewhere (Daniels et al , 2006; Schubauer‐Berigan et al , 2007). Finally, some workers received internal whole body exposures to tritium‐bearing compounds, which were assessed using similar methods.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies indicate that some of this Pu eventually found its way into human beings [Franke et al 1995; Ibrahim et al 2002; International Commission on Radiological Protection (ICRP) 1986; Kathren 2004; O’Donnell et al 1997; Taylor 1995]. There are also a few cases of accidental contamination of humans with Pu via wounds or the inhalation of particles in the workplace (Daniels et al 2006; Filipy et al 1994; Kathren 2004; Krahenbuhl et al 2005; Russell et al 2003). The current systemic biokinetic model for Pu in humans recommended by the ICRP (1993) has been discussed in Leggett (2003), commenting that extrapolating data obtained from laboratory animals onto humans might not be reliable, particularly for the liver, because of differences among species.…”
mentioning
confidence: 99%